ANALISIS EKONOMIS REVITALISASI FLOATING DOCK 9000 TLC DI PT. DOK & PERKAPALAN KODJA BAHARI UNIT GALANGAN 1 JAKARTA - Rofidah Aviani, (2021)
PT. Dok & Perkapalan Kodja Bahari Galangan 1 is one of the shipyards which has main facilities in the form of two floating dock, namely the Jayakerta 3 and Jayakerta 4, but in 2017 the Jayakerta 4 suffered heavy damage which affected the effectiveness of ship repair and maintenance at PT. Dok & Perkapalan Kodja Bahari Galangan 1 Jakarta, The damage of Jayakerta 4 caused by a long service life, which has been operating since 1950, this accident causing disruptions to the productivity and financial rate of shipyard. The revitalization was held in 2020 with the replacement of floating dock Jayakerta 4 to Kalpataru 9000 TLC. The revitalization of the floating dock replacement carried out by PT. Dok & Shipping Kodja Bahari Galangan 1 Jakarta aims to restore productivity and income from the shipyard, but the revitalization that has been carried out is constrained by the shallow water around floating dock area, therefore floating dock operation cannot work optimally and affects the maximum revenue target from the shipyard. This research was conducted with the aim of calculating the investment value of the revitalization of the dock that has been carried out by PT. Dok & Perkapalan Kodja Bahari Unit Galangan 1 Jakarta related to the obstacles that occurred. The methods in this research are field studies for direct observation of floating dock revitalization and interviews to obtain information, as well as primary and secondary data collection for analysis using the break even point (BEP) and Payback Period (PBP) methods.